Field apple scab susceptibility of a diverse Malus germplasm collection identifies potential sources of resistance for apple breeding - David Papp; Liqiang Gao; Ranjita Thapa; Dan Olmstead; Awais Khan (CABI Agriculture and Bioscience)
Abstract Background Breeding for resistance to apple scab (caused by Venturia inaequalis), the most devastating fungal disease of apples, relies on genetic resources maintained in germplasm collections. Methods To identify new sources of scab resistance, we evaluated 177 Malus accessions, including 27 primary and 13 hybrid Malus species from diverse geographical origins, in an orchard at Geneva, New York. We also screened a differential host set for 2 years to monitor for changes in the effectiveness of ten known scab resistance genes, which allowed us to confirm the presence of virulent pathogen races in the orchard. Results We found that ~ 37% of the wild Malus accessions and domesticated cultivars were resistant to apple scab in the field. Several of these accessions were unrelated to sources of previously known resistance genes and are promising for apple scab genetic research and resistance breeding. Cultivars carrying the Rvi6 (Vf) gene from Malus floribunda clone 821, e.g. ‘Liberty’ or ‘Florina’, remained resistant despite the breakdown of Rvi6. ‘Demir’, a Malus hybrid from Turkey, and ‘Chisel Jersey’, a traditional English hard cider cultivar, showed fewer symptoms than the Rvi6 resistant cultivar ‘Prima’. Races 1 to 7 and 9 of V. inaequalis were present in the orchard, but no scab was observed on the indicator host accessions for races 11 and 12. Conclusions Detailed and systematic screening of Malus germplasm identified resistant and moderately resistant donor accessions based on resistance reaction types. These accessions are promising for use in future genetic studies to identify novel sources of scab resistance alleles for apple breeding to develop cultivars with durable apple scab resistance.